I have rights too! - Gremm, Heidi, ....-; Aide et Action International; Kawlra, Vandana, ....-; Narula, Sureeta, ....-; Marboeuf, Olivier, ....- (Paris : Don Quichotte éditions, 2009)
In India, the giant Samvridh is forced to leave school to help his poor parents in the fields. In Congo, Dorothée and Jérémie are enlisted by soldiers whom they mistake for angels. Noï, who leaves his home to beg in the Laotian capital, is hounded by an evil genie. Asha, an Indian girl, is sent to work as a domestic in the home of ogres, whereas Eve-Line turns herself into an aqueduct to supply water to everyone in her village in the Dominican Republic. In Senegal, Jan metamorphoses into a donkey when soldiers chase him out of his village. Every evening José looks up at the sky and dreams of becoming a pilot. On the other hand, Nuray, a Kudish girl who had lost her voice, suddenly starts speaking again once she's back on the benches at school. To celebrate the 20th anniversary of the Convention on the Rights of the Child, Aide and Action has eight stories to tell, illustrating eight rights, selected among the most representative in the Convention.
Celebrates 20 years of rights of the child
Keywords: Kinderrechten